CRITICAL READING SKILL AND ITS IMPLICATION TO SPEAKING ABILITY IN MULTICULTURAL CLASSROOM - Diah Retno Widowati; Kurniasih Kurniasih (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2018)
People need good background knowledge before they speak. The purpose of the present study was to discuss the implication of students’ critical reading skill to their English speaking performance in classroom activity. Researchers also would like to discuss the effect of multicultural atmosphere to students’ speaking skill. This study employed descriptive qualitative design to explain students’ speaking ability after they read. Therefore, students’ speaking ability could be mapped out after being stimulated by critical reading. The major finding of this study were the fact that reading and analyzing the texts was important for students before they speak. Gaining previous information before students speak made them feel more comfortable and be able to deliver or speak up their ideas better. Besides, the multicultural background of the students were not significantly affect their speaking ability. Yet, some students felt difficult in pronouncing ‘f’ in ‘of’, ‘v’ in very’, and ‘o’ in open’ correctly. This was because of their pronunciation habit in their homeland.